Análisis de situación de la microempresa “víveres los pericos” con fines de expansión, parroquia Viva Alfaro, cantón Quevedo año 2012 - Alarcón Flores, Jessenia Elizabeth (2012)
This research develops Groceries microenterprise "The Perishers", which exists since 2006, located in the parish Alfaro live on 21st Street and Abdón Calderón ava city of Quevedo, with the passage of time has growing because they knew they lacked the nesecidades reconer clientele. Offering quality products to the basket of Costa and Sierra, bazaar items, stationery and Resets for cellular telephony. The main objective of this paper is to analyze the situation in which we find this microenterprise selecting your product information, prices and customers. To implement technological tools that improve the quality of service and allow the expansion of "The Perishers" a new Lotización with good image on target for expansion was achieved increase sales, loyalty from its customers and revenue expectations. It will provide the micro "Groceries The Perishers" of an accounting method, with the acquisition of a cash register with drawer, to issue a ticket sales, allowing you to make a cash journal, thus facilitating inventory opportune time and stocks in his warehouse. also will have a database to track promotions to suppliers. With the economic improvement that is currently Groceries microenterprise "The Perishers" has given opportunity to access credit in the Pichincha Mutualista which will be able to expand this business to a new Lotización, which lacks a business that offers variety in terms of products and service.